Nonlinear optical properties of LLDPE composites with titanium dioxide anatase phase - Nafeesah Yaqub (Elsevier, 2022)
In this research work, the linear and nonlinear optical properties of linear low-density polyethylene (LLDPE) composites with anatase phase of titanium dioxide nanoparticles in different weight percentages are investigated. Solvent casting method have been used to synthesize the thin film of LLDPE/anatase nanocomposites. Thin films are characterized via XRD technique and field emission scanning electron microscope (FESEM). Wrinkles formed on the surface of thin films by adding the titanium dioxide. Linear optical and electrical parameters such as linear absorption coefficient, extinction coefficient, refractive indices, optical conductivity, and dielectric constants at various wavelengths from 190 nm to 2700 nm are determined for different weight percentages of nanoparticles in polymer nanocomposites. Z-scan technique has been employed to explore the nonlinear optical properties using CW laser at 532 nm wavelength. The nonlinearity is examined at various irradiance of laser to study the effect of irradiance on nonlinear optical properties. Pure LLDPE has saturable absorption (SA) at low laser irradiance. As the laser irradiance increases, the nonlinearity behavior turns from SA to reverse saturable absorption (RSA). The results show the suitability of the thin films for the applications in optical devices that involve the use of optical limiting properties of materials.